2017
DOI: 10.1002/2017gl074359
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Eddies Control the Timing of Spring Phytoplankton Blooms: A Case Study in the Japan Sea

Abstract: Satellite Chlorophyll a (CHL) data were used to investigate the influence of mesoscale anticyclonic eddies (AEs) and cyclonic eddies (CEs) on the timing of spring phytoplankton bloom initiation around the Yamato Basin (133-139°E and 35-39.5°N) in the Japan Sea, for the period 2002-2011. The results showed significant differences between AEs and CEs in the timing and initiation mechanism of the spring phytoplankton bloom. Blooms were initiated earlier in CEs which were characterized by shallow mixed-layer depth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 61 publications
3
19
1
Order By: Relevance
“…The objective of this study is to investigate the importance of turbulent convective mixing on bloom initiation in AEs and CEs based on model simulation. Thus, we verify the hypothesis of Maúre et al () for bloom initiation in the eddies. We first simulate the ecosystem dynamics associated with mesoscale eddies using a 1‐D coupled turbulence physical‐biological model forced by climatological atmospheric conditions averaged in the interior of eddies.…”
Section: Introductionsupporting
confidence: 91%
See 3 more Smart Citations
“…The objective of this study is to investigate the importance of turbulent convective mixing on bloom initiation in AEs and CEs based on model simulation. Thus, we verify the hypothesis of Maúre et al () for bloom initiation in the eddies. We first simulate the ecosystem dynamics associated with mesoscale eddies using a 1‐D coupled turbulence physical‐biological model forced by climatological atmospheric conditions averaged in the interior of eddies.…”
Section: Introductionsupporting
confidence: 91%
“…Maúre et al () found that the MLDs in eddies are different and that they have different annual cycles. In AEs, maximum MLD was observed around March whereas in CEs the MLD shallows from January.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Conversely, the well‐mixed conditions due to frequent and enhanced storm events can explain the regional fall blooms when accompanied by sufficient light conditions and the relatively limited nutriments resulting from the spring bloom and subsiding levels of chlorophyll concentrations during the summer (e.g., Kim et al, ; Yoo & Park, ). In this region, the vertical stratification exhibits seasonal and its superharmonic variability ( SA 1 , SA 2 , and SA 3 ), which can amplify the blooms in spring and fall due to the local deepening of the MLD, which is slightly different from the bloom initiation due to the relaxation of turbulent mixing at the end of the winter (e.g., Huisman et al, ; Maúre et al, ).…”
Section: Resultsmentioning
confidence: 99%